Pop Culture and Islamic Identity of Millennials and Gen Z: Hijabers, Muslim YouTubers, and the Contestation of Modest Fashion Meaning - Toyyib, Moh.; Yunus Musthofa, Muhammad; Putri, Sajida (Surau Journal of Islamic Studies, 2026)
This study examines the construction and contestation of Islamic identity among Millennials and Generation Z within the landscape of digital popular culture, specifically through the phenomena of hijabers, Muslim YouTubers, and modest fashion. The analysis employs a library research methodology, systematically reviewing scholarly literature to explore how religious values, aesthetics, and digital capitalism intersect in shaping contemporary Muslim identities. Findings reveal that social media functions as a crucial arena where piety is increasingly expressed through performative and aesthetic practices, leading to a dynamic negotiation between authenticity and commodification. The study concludes that Islamic identity in the digital age is fluid and hybrid, marked by a shift from traditional religious authority toward participatory, algorithmically mediated forms of religiosity. These transformations highlight the need to critically re-examine the relationships between religion, media, and popular culture in increasingly digitized Muslim societies.